Reimagining organisational responses to domestic and family violence: applying a feminist ethics of care to the work–violence interface in non-metropolitan Victoria, Australia. (2nd October 2022) - Farhall, Kate; Quek, Kaye; McVey, Laura
ABSTRACT: In this article, we apply the theory of feminist care ethics to the issue of workplace responses to domestic and family violence (DFV). Specifically, we aim to understand how prevailing approaches to the intersection of violence and work can be reoriented to centre feminist principles of care, distinct from the masculinist logics on which they currently rely. Our discussion draws on semi-structured interviews with experts on the work–violence interface, primarily based in the non-metropolitan Gippsland region of Victoria, Australia. It identifies three key themes, consistent with feminist care ethics, which can be used as a basis for reimagining workplace responses to DFV: 1) the importance of attentiveness as a practice of care; 2) the need to reimagine employer responsibility for a more caring and gender-equal workplace; and 3) the value of flexibility in responding to DFV. We argue that the data highlight the need for workplaces to structurally embed care in their initiatives on DFV. The analysis also points to the transformative potential of approaches in which care is centred, though, at present, these examples are the exception rather than the rule.